Letter - Price, John, 1901-
028-0167-001 INTERNATIONALE OUVRIERE SOCIALISTE LABOUR AND SOCIALIST INTERNATIONAL SOZIALISTISCHE ARBEITER-INTERNATIONALE Secrétariat: BRUXELLES, 162, rue de Laeken Adresse télégraphique - Telegrams - Telegrammadresse: INTERSOCIA BRUXELLES Téléphone : 17,70,36 et 17,70,37 P/V. BRUXELLES, October 23rd, 1936. Mr. H. V. Tewson, Assistant Secretary, Trade Union Congress General Council, Transport House, Smith Square, London, S.W.1. Dear Comrade, We wish to acknowledge in Dr. Adler's absence your letter of October 20th, in which you state that the position of the Fund for the Spanish Workers which has passed through your hands is as follows :- Amount raised in Great Britain: £18,731.18.6d. Remittance from America: £7,102.0.0. You will be interested to know that a consignment of 100 tons of foodstuffs (articles indicated on a list supplied by the Spanish Committee of the International Solidarity Fund) has been sent at our instructions to Spain, where it was due to arrive this week. A further consignment is being prepared and we are hoping that this will be sent off during the coming week. We also understand that a supply of clothing asked for by the Spanish Committee is being obtained by the I.F.T.U. Yours sincerely, John Price. 292/946/28/167